2020
DOI: 10.1016/j.biologicals.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a standardised Vi poly-l-lysine ELISA for serology of Vi capsular polysaccharide antibodies

Abstract: Typhoid vaccines based on protein-conjugated capsular Vi polysaccharide (TCVs) prevent typhoid in infants and young children. Analysis of the serum anti-Vi IgG response following immunisation against typhoid confirms the immunogenicity of TCVs and forms an important part of the pathway to licensing. Comparative studies could expedite the licencing process, and the availability of a standardised ELISA method alongside the 1st International Standard (IS) 16/138 for anti-typhoid capsular Vi polysaccharide IgG (hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Following the request of the WHO Expert Committee on Biological Standardization (ECBS), Vi-PLL ELISA has been finally assessed in 2020 as a suitable substitute to the VaccZyme ELISA, allowing to use this uniform non-commercial, and thus more available, method to use at a lower cost. The Vi-PLL procedure is publicly available and uses standard biological agents, as opposed to VaccZyme (WHO 2018 ; Rigsby et al 2020 ). Key considerations for implementation and smooth performance are the level of reagent standardisation (reference standard), validity criteria (system and sample suitability) and the inclusion of assay-specific run controls which may be study samples representative of Vi PS vaccines (Rigsby et al 2020 ).…”
Section: Part IImentioning
confidence: 99%
See 2 more Smart Citations
“…Following the request of the WHO Expert Committee on Biological Standardization (ECBS), Vi-PLL ELISA has been finally assessed in 2020 as a suitable substitute to the VaccZyme ELISA, allowing to use this uniform non-commercial, and thus more available, method to use at a lower cost. The Vi-PLL procedure is publicly available and uses standard biological agents, as opposed to VaccZyme (WHO 2018 ; Rigsby et al 2020 ). Key considerations for implementation and smooth performance are the level of reagent standardisation (reference standard), validity criteria (system and sample suitability) and the inclusion of assay-specific run controls which may be study samples representative of Vi PS vaccines (Rigsby et al 2020 ).…”
Section: Part IImentioning
confidence: 99%
“…The Vi-PLL procedure is publicly available and uses standard biological agents, as opposed to VaccZyme (WHO 2018 ; Rigsby et al 2020 ). Key considerations for implementation and smooth performance are the level of reagent standardisation (reference standard), validity criteria (system and sample suitability) and the inclusion of assay-specific run controls which may be study samples representative of Vi PS vaccines (Rigsby et al 2020 ).…”
Section: Part IImentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that due to tourism also the bacteria spreads across the various European countries and USA [3]. The rate of risk of infection is severe in countries in the continents of Asia, Africa, and Latin America where poor sanitation is observed [7]. Typhoid fever is mostly observed in underaged children and school going children.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are two quite distinct vaccines that are available in the market. One oral live attenuated vaccine that contain strain Ty21a and Vi polysaccharide vaccine administered parenterally [7]. The oral typhoid vaccine is given in the form of enteric capsules as three to four doses [8].…”
Section: Introductionmentioning
confidence: 99%